Surgical Management of Locally Advanced Breast Carcinoma Following Neoadjuvant Chemotherapy (Journal of Surgical Sciences, 2022)
Background: Locally advanced breast cancer is still a common form of presentation of breast cancer in developing countries like Bangladesh. Large number of studies and many randomized trials has been done in women with LABC in order to improve the therapeutic decisions and also the local control and survival.Objectives: To evaluate the different surgical modalities that patients received after neoadjuvant chemotherapy for LABC.Methodology: This is a prospective observational study conducted among admitted patients having locally advanced breast carcinoma following neoadjuvant chemotherapy from December 2018 to December 2019.Result: Demographic features showed that, maximum patients age range was 41-50 years, mean age was 43.66 years. Out of 38 cases 17(44.74%)cases were ER positive, 11(28.95%) case were progesterone positive, 4(10.53%)cases were her-2 receptor positive and 17(44.74%)cases were triple negative breast cancer(TNBC). Lymphovascular invasion was present in 39.47% cases. Commonly performed surgical procedures were modified radical mastectomy (89.47%), breast conserving surgery with sentinel lymphnode biopsy (5.26%), LD flap coverage (2.63%), toilet mastectomy (2.63%). After mastectomy only 2(5.26%) patient showed margin involved and one patient developed marginal necrosis.Conclusions: Modified radical mastectomy still remains the standard of care in the surgical management of LABC in this study.Journal of Surgical Sciences (2022) Vol. 26(1) : 5-9